Obustronny oponiak osłonek nerwu wzrokowego (ONSM) – problemy diagnostyczne i lecznicze - Chipczyńska, Barbara; Grałek, Mirosława; Trzebicka, Agnieszka; Hautz, Wojciech; Kanigowska, Krystyna; Klimczak-Ślączka, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
The authors describe the case of bilateral optic nerve sheath meningioma /ONSM/ in 14 years old girl. When being hospitalized at the Neurology Clinic with paresis n.VII, the patient was examined by ophthalmologist. The diagnosis was made on the basis of clinical and characteristic changes revealed by USG, CT and MRI. The very first ophthalmologic examination confirmed a visual acuity 5/5 OD and hand movements OS, associated with papilloedema OD and edematous optic atrophy OS. The use of USG, CT and MRI revealed bilateral tubular thickening of the optic nerves (8mm), with calcification. After the period of one year, clinical progression was observed. The intracranial tumor extended. It was shown in diagnostic imaging. The patient was operated on by neurosurgeons with histopathology verification. In the later stage she underwent radiotherapy. The case has been described because of its diagnostic and therapeutic difficulties.